Communication Styles of Wives with Smoking Husbands in Protecting Their Babies from Cigarette Smoke Exposure at Home - Desy Safitry; Leila Mona Ganiem (Ikatan Sarjana Komunikasi Indonesia, 2024)
Exposure to cigarette smoke in the home poses significant health risks, particularly to infants and toddlers. This study explores the communication styles used by wives to encourage their smoking husbands to quit or reduce smoking to protect their children’s health. A qualitative approach was employed, utilizing a constructivist paradigm with in-depth interviews conducted among mothers of toddlers with smoking husbands. The findings reveal that while most wives possess good knowledge about the dangers of smoking, they face challenges in persuading their husbands to quit. The most common communication style used was passive, influenced by cultural norms, education levels, and social support. While assertive communication was more effective in reducing smoking habits, it was less frequently employed. The study concludes that broader interventions, such as community-based programs and education for both parents, are necessary to promote smoke-free environments for children. Training and social support are recommended to improve communication effectiveness in encouraging smoking cessation.